DEVELOPMENT OF WORDWALL-BASED E-LKPD TO IMPROVE FIQIH LEARNING OUTCOMES AT STATE SENIOR HIGH SCHOOL 1 ULU BARUMUN - Nasution, Intan Permatasari (FORUM PAEDAGOGIK, 2025)
This study focuses on the development of Wordwall-based Electronic Student Worksheets (E-LKPD) to enhance learning outcomes in Islamic Religious Education (PAI), particularly in the fiqh element, at SMA Negeri 1 Ulu Barumun, Padang Lawas Regency, North Sumatra. The background of this research is the relatively low interest and learning achievement of students, caused by the dominance of lecture-based methods and the limited use of conventional worksheets. Using a Research and Development (RD) approach with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), the study involved 32 students of class XI IPA-1. The developed product was validated by media, language, and material experts, resulting in feasibility scores of 85.45%, 90%, and 88%. Student trials also showed very positive responses with an engagement rate of 91.78%. The findings reveal that the Wordwall-based E-LKPD is highly feasible and effective in improving student learning outcomes. Moreover, it fosters digital literacy and creates a more interactive, engaging, and contextual learning atmosphere. This innovation also holds potential for application in other subjects as a digital learning solution.